Evaluation of gabions usage effectiveness for industrial facilities protection against damage - Medvedieva, O. O.; Dziuba, S. V.; Kalashnikov, I. V.; Biliaiev, M. M.; Kozachyna, V. A. (Science and Transport Progress, 2025)
Purpose. In the extreme situations at industrial sites, various damaging factors may appear, such as the spread of toxic substances in the air, the creation of a fireball, etc., which pose a threat to the lives of workers and have a significant negative impact on the environment. That is why today, special attention is being paid to the problems associated with the spread of debris during a drone attack. At an industrial site where oil product storage facilities are located, the debris generated during an explosion can damage the tank building and cause a fire. In this regard, the main objective of the study is to evaluate the effectiveness of using gabion to reduce the risk of damage to the oil storage facility during the movement of drone debris. Methodology. To achieve this goal, the paper considers the problem of flying debris in the event of a drone explosion at an industrial site where oil storage facilities are located. The use of gabion with sand is proposed to protect the tank building from the throwing effect of debris. It is proposed to develop a mathematical model of the movement of a fragment in the path of which the gabion is located. The effect of gabion as a protective screen on reducing the air temperature near a neighboring oil storage facility in the event of a fire at an industrial site is also considered. A model of the dynamics of a point motion (Newton's second law) was used to mathematically describe the movement of the debris. Numerical integration of the modeling equations was performed using the Euler's method. The energy equation was used to model the process of thermal air pollution at an industrial site during a fire. Findings. In this work, the numerical model was programmed and a computer code was created. The programming language is FORTRAN. The code provides information on the speed of the fragment movement in different parts of each zone. On the basis of the constructed numerical model and the created code, parametric studies were carried out to determine the effectiveness of using gabion with sand to protect the oil storage facility from the effects of fragment. As an approximation, the case when the fragment after the explosion moves horizontally in the direction of the object was considered. The influence of the gabion height on the heating level of the wall of the oil storage facility located at an industrial site was analyzed. Originality. An effective mathematical model has been developed to evaluate the effectiveness of using gabion to protect the oil storage facility from damage by drone fragment. The proposed model allows determining the rational dimensions of the gabion to reduce the risk of damage to the tank wall. An effective computer model of thermal air pollution at an industrial site in the event of a fire at an oil storage facility is presented. Practical value. On the basis of the constructed mathematical model, a computer code was created to conduct a computational experiment to determine the effectiveness of using protective barriers (gabions) on the territory of an industrial site.